Eribulin in Heavily Pre-Treated Metastatic Breast Cancer: A Case Series - Kartikasari, Andini; Oehadian, Amaylia (International Journal of Integrated Health Sciences, 2025)
Background: Treatment options are limited for heavily pre-treated metastatic breast cancer patients, with Eribulin showing promise in improving survival outcomes.Objective: To evaluate Eribulin outcomes in patients with MBC. Metastatic or incurable diseases are observed in 4% to 10% of women despite advances in breast cancer treatment. To address this problem, EMBRACE, an important randomized phase III clinical trial was carried out by comparing eribulin to the treatment selected by physicians for individuals with previously treated locally recurrent or metastatic breast cancer (MBC). The results showed a significant and prolonged increase in median overall survival among patients treated with eribulin, compared to those who received the physician's selected treatment.Case Series: This study presents three patients who showed favorable outcomes after treatment with eribulin, despite multiple lines of previous therapy. Patient 1 was diagnosed with triple-negative breast cancer and initially achieved remission before experiencing a recurrence involving a chest lesion and enlarged lymph nodes. After two cycles of eribulin, the patient showed significant improvement. Patient 2 developed brain and liver metastases following the completion of hormonal therapy, prompting the initiation of eribulin as the next line of treatment. Patient 3 had disease progression despite undergoing multiple lines of hormonal and chemotherapy. Eribulin was administered and patient remained stable.Conclusion: Patients with MBC tend to have substantially favorable outcomes with eribulin chemotherapy even after extensive previous treatment.